Vyāsa’s Bakavadhaparvan: A Source for Bhāsa’s Madhyamavyāyoga - Roberto Morales-Harley (Studia Orientalia Electronica)
As its primary/explicit source, the Madhyamavyāyoga has the Hiḍiṃbavadhaparvan, where Bhīma kills Hiḍiṃba and marries his sister Hiḍiṃbā. As a possible secondary/implicit source, it also has the Bakavadhaparvan, where Bhīma kills Baka and ends up saving a Brahman and his family. This paper proposes a comparison between the two epic sources, on one hand, and the dramatic adaptation, on the other, to determine the key features of such supposed merging. To that end, it examines (1) psycho-affective components (sneha), (2) socio-cultural components (dharma), and (3) religio-philosophical components (toya/jala). The main conclusion is that, on these subjects, the resemblances of the play with the story of Baka are more significant than those with the story of Hiḍimba.